Exploring XML Schema Styles Using JAXB in Enterprise Applications choose the right XML schema for your enterprise applications. - Varma, Pushkar
Code generation tools are capable of significantly impacting productivity and are now an essential part of a developer's tool set. There are two categories of transformation tools : those whose output is used by software components and those whose output is used by developers. With tools that generate output for developers, it becomes important to properly design the input to these tools so that the output is comprehensible and usable, and the input is maintainable by developers. Java Architecture for XML Binding (JAXB) is one such tool that takes an XML Schema file as input, and transforms this input into a Java class model that is usable directly by a developer. Since an essential part of any application is its information model, it becomes important to properly design the XML Schema so that the generated class model is comprehensible and usable and the schema itself is maintainable and reusable.